The Acquisition of English Vocabulary for Children at Grade III in SD Islam Nurul Hidayah - Albiansyah Albiansyah; Fahriany Fahriany (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
AbstractThis study is an effort to understand the acquisition of the English language by students at SD Islam Nurul Hidayah in Bojong Sari. The aim of this study is to identify and evaluate the acquisition of the English language by students at SD Islam Nurul Hidayah in Bojong Sari. The use of simple statistical analysis response research query, a qualitative approach was used. This study used the theory on telegraphic and formulaic speech from Tabors and Snow. In this study, there were 17 students as samples and the collection of data techniques was taken through interviews.The results of the interviews indicate that the development of English language vocabulary by children is in two stages (telegraphic/formulaic expression and constructive language): body part is 39% telegraphic and 61% productive, transportation is 62% telegraphic and 38% productive, color is 44% telegraphic and 56% productive, classroom is 40% telegraphic and 60% productive, job is 45% telegraphic dan 55% productive, nation is 43% telegraphic and 57% productive, universe is 81% telegraphic and 19% productive, self-introduction is 57% telegraphic and 43% productive, prayer before learning is 100% with 0% productive language, and prayer after learning is 100% and 0% productive language. This study then recommends that the teacher of SD Islam Nurul Hidayah in Bojong Sari increase the student's motivation to learn English and to practice English more frequently. It is recommended to do further research focusing on students in preschool or kindergarten to examine their acquisition of English. Keywords: Second Language Acquisition; Children; Elementary School